REPERTOIRE OF CINEMAS AND AUDIENCE PREFERENCES IN THE ERA OF "STAGNATION" - M. Kosinova (Publishing House of the State University of Management, 2016)
The article deals with the repertoire policy of Soviet cinema in the 1970's - early 1980-ies. By studying such aspects as genre and thematic range, the plots, the characters, etc., the author tries to reveal the relationship between changes taking place in society at the time, and cinema as a repeater these changes. In particular, the strengthening of censorship in the era of stagnation leads to the fact that the vast majority of directors "breaks" under the weight of the system and continues to work by inertia - in the space of canonical Communist ideas and the Soviet conception of life. These worldviews continue to run in the conveyor of the Soviet film industry, which automatically gives the most part of its products smack of falsehood, which cannot fail to perceive the viewer. Largely for this reason, in the 1980-ies our movie will be in poor condition.